Politeness Strategies for the Speech Acts of Indonesian Language Education Students in Pidie Regency - Saputra, Nanda; Lubis, Tasnim; Setiawan, Fitria (TALENTA Publisher, 2021)
This study aims to describe the strategy of politeness in speech acts of final semester students of Indonesian Language Education at Pidie. This research focuses on the strategies of politeness speech acts used by the final semester students of Indonesian Language Education in Pidie Regency in communicating. This research was conducted with a qualitative approach. This research is a type of field research. The research was carried out in six stages: (1) making and distributing data source information instruments, (2) classifying the results of data collection as a reference for data collection, (3) recording student conversations when communicating freely in public places (4) transcribing data obtained by recording, (5) analyze and describe the research results carefully, (6) calculate the percentage of occurrence of each type of speech act politeness strategy used by students in communicating. The results showed that the final semester students of Indonesian Language Education in Pidie Regency used three of the four speech act politeness strategies, namely the type without a strategy, the type of positive politeness strategy, and the type of negative politeness strategy.